2017
DOI: 10.1007/s12325-017-0528-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Measures of Adjustable Transobturator Male System with Pre-attached Scrotal Port for Male Stress Urinary Incontinence After Radical Prostatectomy: A Prospective Study

Abstract: Treatment of severe male SUI after radical prostatectomy with pre-attached scrotal port ATOMS is safe and very effective in the short term. A positive cough test before implant and intraoperative overfilling of the system may optimize patient selection and results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 26 publications
4
36
0
1
Order By: Relevance
“…Later a singlecenter experience confirmed that ATOMS represents an efficient alternative even for severe incontinence [29]. Also, patient-reported outcomes showed ATOMS is a well-appreciated option for SUI of any severity [12].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Later a singlecenter experience confirmed that ATOMS represents an efficient alternative even for severe incontinence [29]. Also, patient-reported outcomes showed ATOMS is a well-appreciated option for SUI of any severity [12].…”
Section: Discussionmentioning
confidence: 89%
“…However, titanium intolerance was the most frequent complication leading to explant in this series, associated to IP, an outdated design of device not used in our series. Also, incontinence severity and previous irradiation appear risk factors for ATOMS failure [12,14], but it should be taken into account that these are also risk factors for retropubic sling and AUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urethral compression can be adjusted postoperatively by filling or emptying the cushion by the simple injection of sterile liquid through the port, without anesthesia or fluoroscopic guidance. It opens a new perspective of treatment for patients with mild‐to‐moderate forms of SUI and can be the best option in patients with limited dexterity or cognitive impairment and SUI of any degree . However, there are still great uncertainties concerning optimal patient selection and durability of the ATOMS device which can only be overcome by increasing the experience with the device.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Interestingly, patient-reported outcomes (PROs) with the device confirm a high level of satisfaction can be expected, but not all patients achieve continence after the implant. 12,13 Several clinical and urodynamic risk factors can be responsible for urinary incontinence persistence after surgical treatment of PPI but, due to their different mode of action, they may differ between surgical devices used. For AUS, persistence of urethral sphincter dysfunction and urodynamic filling phase disorders, like diminished bladder compliance and higher detrusor overactivity (DO) pressure, have been proposed as determinants for failure of surgical treatment of PPI and persistent incontinence.…”
Section: Introductionmentioning
confidence: 99%